Innovative methods of teaching and harmonization of educational standards in the sphere of computing - Alekseyev, M. A.; Chernyshenko, V. S.; Loza, T. J. (Sumy State University, 2013)
Competence-based approach to education (unlike traditional qualification) reflects requirements not only to the content of education, but also to a behavioral component. Recommendations about drawing up curricula for training of specialists in the computing sphere are considered. New pedagogical methods, proposing creative combination of the theory and practice which is reached in the course of direct professional activity are analyzed. The analysis of the problems arising at creation of educational standards is also given. It has shown that professional standards are primary link in high-quality training of various areas of economy specialists (including for computing area), and also ensuring their competitiveness have to be a basis for their development. Thus, problems when developing professional standards complicate prospect of harmonization of professional and educational standards which demands necessary methodological, methodical and expert completion at the first design stage.
Keywords: computing, curricula, educational standards, competence-based approach, cases